Experimental study on effective stress sensitivity of coal permeability based on dynamic drainage process - Kang LI; Xiaoyang ZHANG; Binbin HU; Weijiang KONG; Yunfei DOU; Junjian ZHANG; Dongdong WANG (Meitan kexue jishu, 2025)
The dynamic changes in reservoir permeability during coalbed methane well drainage largely depend on variations in effective stress and pore structure. It is very important to analyze the stress sensitivity of coal reservoir to understand the dynamic change effect of reservoir drainage and production. Based on this, coal samples from the No. 3 coal seam in the Sihe Mine on the southeastern edge of the Qinshui Basin were collected. The pore and fracture distribution characteristics of coal were analyzed using CT scanning and nuclear magnetic resonance (NMR) techniques. Helium permeability tests of coal samples with different water saturation under variable pore pressure were carried out. The effective stress coefficient (ESCK) of coal permeability was obtained by the response surface method. Based on the improved S&D model, the dynamic change law of permeability was analyzed according to the actual drainage process. The results show that the NMR T2 spectra of coal samples in dry and saturated water state are approximately unimodal distribution, and the pore structure is dominated by micropores. SK1 sample has a penetrating main fracture and good continuity of diffusion pore and seepage pore, which can provide seepage channel, resulting in better permeability than SK3 sample. For the same water saturation, permeability decreases with increasing net stress, showing a good power-law fitting relationship between them. As water saturation increases, the permeability of coal samples decreases with increasing net stress under the same pore pressure, following a power-law fitting relationship. The relationship between conversion permeability (k') and confining pressure and pore pressure is binary linear. The ESCK values of coal samples with different water saturations are constant and significantly less than 1.0, ranging from 0.244 5 to 0.475 3. The effective stress of coal reservoir is greater than the net stress, and the permeability stress is sensitive, which has greater influence on the permeability. The drainage system should be formulated reasonably to avoid excessive drainage and pressure reduction rate.